HISTORICAL ANALYSIS OF THE PROBLEMS OF TEACHER SHORTAGE IN THE PUBLIC EDUCATION SYSTEM - Nargizakhon, Sharipova (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to analyze the historical causes of teacher shortages in Uzbekistan, examining their impact on the quality of education and evaluating the effectiveness of government interventions in addressing the issue. Method: A historical-analytical approach is employed, drawing on archival records, policy documents, and statistical data to trace the evolution of teacher shortages across different periods. Comparative analysis is used to assess the outcomes of various policy measures and their long-term implications. Results: The findings indicate that teacher shortages in Uzbekistan have been persistent due to factors such as rapid population growth, inadequate teacher training infrastructure, and competition from alternative employment sectors. While government interventions, including financial incentives and recruitment policies, have shown some success, they have not fully resolved the issue, particularly in rural and underserved areas. Novelty: This study contributes to the discourse on teacher shortages by providing a comprehensive historical perspective, linking past and present challenges to policy effectiveness. Unlike previous studies that focus solely on contemporary issues, this research highlights the structural and systemic factors that have shaped the problem over time, offering insights for more sustainable solutions.